Upaya-upaya pelenyapan peradaban Islam - Sa’diyah, Halimatus (Maliki Interdisciplinary Journal, 2024)
The history of Islamic civilization is the events or events that occured in the Islamic period where at that time Islam was mainstay of power. If we look back, the civilization of the Islamic world has suffered a crushing blow in the consistency of civilization. This causes a decline. Meanwhile, Islam retread because it abandoned the intellectual traditions that had previously been developed. And the tradition was subquently taken back by western people.